DOCUMENTING UNDOCUMENTED THE WAY INI TRANSLATION OF STUDENTS IN JUNIOR HIGH SCHOOL - Efriza, Dony; Yelia, Yelia; Adimarta, Teguh; Yusrizal, Yusrizal (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to give information about qualitative findings on students’ translation strategy used by students in the private Junior High School in Indonesia. There are 22 partcipants of this study. Observation and interview were used in collecting data for this study. This study used qualitative research, the aims was to get more information about translation strategy of the students in the Juior High School. The most strategies used by students was Literal translation, the score were 153 from 23 sentences of narrative text. The students says that “Interpreted by literal to make it easier and I always use the dictionary when translating”. It adds also by teacher that “the most students translate the text by literal, and used dictionary”. The highest score was not affected by translating strategy. However, the highest score obtained based on the effective translation or the translation results that contain the same meaning of the source language to the target language.